Analisis Fraud Pentagon Dalam Mendeteksi Kecurangan Laporan Keuangan (Studi Kasus Pada Perusahaan Sektor Healthcare Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021) - Evaldiana Adelia; Wilhelmina Mitan; Fransiscus De Romario (Student Scientific Creativity Journal, 2023)
This study aims to determine the effect of pentagon fraud in detecting financial statement fraud in healthcare sector companies listed on the Indonesia Stock Exchange in 2021. The method used in this research is quantitative in nature causative with data sources in the form of secondary data. The sample of this research is 21 companies in the healthcare sector using a purposive sampling method. The data for this research were obtained from literature and documentation. The results of this study show that partially financial target variables and changes in directors have an effect on fraudulent financial reports in healthcare sector companies listed on the Indonesia Stock Exchange in 2021. Meanwhile, external pressure variables, ineffective supervision, auditor changes, and the frequency of CEO photos appearing have no effect on fraudulent financial statements in healthcare sector companies listed on the Indonesia Stock Exchange in 2021. Simultaneously financial targets, external pressures, ineffective supervision, changes in auditors, changes in directors, and the frequency of CEO photos appearing have an effect on fraudulent financial statements.